Acute oral toxicity effects of Momordica charantia in sprague dawley rats - Rosli, Nurul Husna; Abdullah, Noriham; Hashim, Nooraain; Abdul Hamid, Azizah; Othman, Farah Amna (IACSIT Press, 2013)
Momordica charantia is commonly known as bitter gourd, balsam pear or karela is a multi-purpose herb. It is cultivated from different parts of the world and is usually used in traditional medicine. This study was conducted to investigate the acute oral toxicity effects of Momordica charantia in Sprague Dawley rats based on OECD Guidelines 423. The extract was administered orally at two different doses of 300 mg/kg and 2000 mg/kg of body weight. The toxicity signs were recorded within the first 24 hours after forced feeding. Both of the treated groups showed dizziness and depression during the first 30 minutes. However, no significant difference of feeding patterns which included water, food intake and body weight gain were observed. Haematological evaluations did not show significant differences in white blood cells count (WBC), mean corpuscular volume (MCV) and mean corpuscular haemoglobin concentration (MCHC) levels. However, red blood cells count (RBC) and packed cell volume (PCV) percentage was significantly lower in rats that received 2000 mg/kg than those of the other two groups. Meanwhile, haemoglobin (Hb) count and the relative liver weight of rats received 2000 mg/kg body weight of extract decreased significantly (p<0.05) as compared with the control group. Thus, this study is expected to be beneficial for clinical and traditional applications for safe consumption and to utilize Momordica charantia as a remedy at a recommended dosage.